A World of Differences: Image, Identity and Reality in Alejandro Iñarritu’s Babel - Mancelos, João de (2011)
Do our religious, political, cultural and ethnic differences prevail over what we universally share? If so, how compatible are individuals living in countries as different as Morocco, Japan, the US or Mexico? Divergences and convergences constitute the central theme of Babel (2006), directed by Alejandro Iñarritu, and nominated for seven Academy Awards. Linked by a single incident, several characters are forced to revise their images of the Other, and concurrently of themselves. In this paper, I examine the images, (mis)conceptions and stereotypes characters from different nationalities have of the Other’s identity; how those ideas influence their behavior towards the Other; how those conceptions relate to reality. Understanding the interaction between these aspects contributes to a more precise idea of how conflicts arise and how to approach them.